2019
DOI: 10.1126/scisignal.aat6023
|View full text |Cite
|
Sign up to set email alerts
|

T cell–derived soluble glycoprotein GPIbα mediates PGE 2 production in human monocytes activated with the vaccine adjuvant MDP

Abstract: Vaccine adjuvants containing analogs of microbial products activate pattern recognition receptors (PRRs) on antigen-presenting cells, including monocytes and macrophages, which can cause prostaglandin E2 (PGE2) release and consequently undesired inflammatory responses and fever in vaccine recipients. Here, we studied the mechanism of PGE2 production by human monocytes activated with muramyl dipeptide (MDP) adjuvant, which activates cytosolic nucleotide-binding oligomerization domain 2 (NOD2). In rabbits, admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
(66 reference statements)
1
3
0
Order By: Relevance
“…Experiments using multiple inhibitors showed that DD and IC utilize common as well unique signaling pathways: ERK1/2 MAP kinase was responsible for upregulation of PGE2, IL-6, and IL-8 suggesting that ERK1/2 plays indispensable role in activation of pyrogenic and pro-inflammatory mediators in monocytes activated with DD and IC. Cytosolic [Ca2+] was required for production of PGE2, IL-6, and IL-8 in monocytes activated with DD alone in agreement with our earlier observations that signaling from αMβ2 integrin increases cytosolic [Ca2+] in monocytes [ 46 ]. Interestingly, in monocytes activated with DD in the presence of IC, the contribution of calcium signaling varied as inhibitor of IP 3 R completely blocked PGE2 but not IL-6 or IL-8 production suggesting that production of pro-inflammatory cytokines was partially [Ca2+] independent.…”
Section: Discussionsupporting
confidence: 91%
“…Experiments using multiple inhibitors showed that DD and IC utilize common as well unique signaling pathways: ERK1/2 MAP kinase was responsible for upregulation of PGE2, IL-6, and IL-8 suggesting that ERK1/2 plays indispensable role in activation of pyrogenic and pro-inflammatory mediators in monocytes activated with DD and IC. Cytosolic [Ca2+] was required for production of PGE2, IL-6, and IL-8 in monocytes activated with DD alone in agreement with our earlier observations that signaling from αMβ2 integrin increases cytosolic [Ca2+] in monocytes [ 46 ]. Interestingly, in monocytes activated with DD in the presence of IC, the contribution of calcium signaling varied as inhibitor of IP 3 R completely blocked PGE2 but not IL-6 or IL-8 production suggesting that production of pro-inflammatory cytokines was partially [Ca2+] independent.…”
Section: Discussionsupporting
confidence: 91%
“…When infected with Mtb , human PBMCs with functional NOD2 produced more IL-1 than human PBMCs containing the NOD2 3020insC mutation ( 32 ). MDP also promoted PGE2 production by monocytes and macrophages ( 33 , 34 ). The balance of immune mediators like type I IFN, IL-1 and PGE2 may play a key role in pulmonary cell death during Mtb infection.…”
Section: Discussionmentioning
confidence: 96%
“…The resulting peptides were resolved and analyzed by nanoflow liquid chromatography coupled to tandem mass spectrometry using a Thermo Fisher Ultimate LC and Fusion Orbitrap MS by following typical settings at Food and Drug Administration’s (FDA's) Facility for Biotechnology Resources 28 . For identification, Proteome Discoverer 2.1 (Thermo Fisher Scientific) was used to match tandem mass spectometry spectra to peptides using Swiss‐Prot human database with typical setting as previously reported 29 . For quantification using a label‐free approach, the peptides were quantified by integrating (at 20 ppm tolerance) the signal intensities obtained from extracted ion chromatogram of respective peptides (Table S3).…”
Section: Methodsmentioning
confidence: 99%
“…28 For identification, Proteome Discoverer 2.1 (Thermo Fisher Scientific) was used to match tandem mass spectometry spectra to peptides using Swiss-Prot human database with typical setting as previously reported. 29 For quantification using a label-free approach, the peptides were quantified by integrating (at 20 ppm tolerance) the signal intensities obtained from extracted ion chromatogram of respective peptides (Table S3).…”
Section: Nano Liquid Chromatography Tandem Mass Spectrometrymentioning
confidence: 99%